Virtually No Effect? Different Uses of Classroom Computers and their Effect on Student Achievement - Ludger Wößmann; Oliver Fack; Constantin Mang (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Most studies find little to no effect of classroom computers on student achievement. We suggest that this null effect may combine positive effects of computer uses without equivalently effective alternative traditional teaching practices and negative effects of uses that substitute more effective teaching practices. Our correlated random effects models exploit within-student between-subject variation in different computer uses in the international TIMSS test. We find positive effects of using computers to look up information and negative effects of using computers to practice skills, resulting in overall null effects. Effects are smaller for low-SES students and mostly confined to developed countries.
Keywords: I21; I28; I20; 330